The Effects of Hemiparasitism by Castilleja Species on Community Structure in Alpine Ecosystems - Johannah Reed (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
There is a long history in ecology of examining how interactions such as competition, predation, and mutualism influence the structure and dynamics of natural communities. However, few studies to date have experimentally assessed the role of hemiparasitic plants as a structuring force. Hemiparasitic plants have the potential to shape plant communities because of their ability to photosynthesize and parasitize and because of their abundance in a variety of natural and managed ecosystems. A study was conducted which focused on the impacts of hemiparasitic species in the genus Castilleja, which are ubiquitous in montane meadows in the Colorado Rockies. This study employed a manipulative experiment in which Castilleja was removed from intact communities and surveys were conducted over an extensive elevational gradient to examine the relationship between the natural density of Castilleja and a suite of community-level properties. The experiment showed that the communities in which Castilleja was removed had lower evenness than plots where Castilleja was present. This suggests that the presence of Castilleja promotes evenness or more equal dominance of plant species in the community. The observational study, in contrast, showed no statistical differences in community-level properties in plots with and without Castilleja species present. Taken together, this research demonstrates that hemiparasites do have the potential to shape plant communities in alpine ecosystems, but more research should be done to determine the extent of their effects in natural and manipulated systems.
Keywords: Environment; Hemiparasitism; Castilleja; Ecosystems